Flow and heat transfer in serpentine channels - Karale, Chaitanya M.; Bhagwat, Sunil S.; Ranade, Vivek V. (Aiche Journal, 2013)
Serpentine channels are often used in microchannel reactors and heat exchangers. These channels offer better mixing, higher heat and mass-transfer coefficients than straight channels. In the present work, flow and heat transfer experiments were carried out with a serpentine channel plate comprising of 10 units (single unit dimensions: 1 x 1.5 mm(2) in cross section, length 46.28 mm, D-h 1.2 mm) in series. Pressure drop and heat-transfer coefficients were experimentally measured. Flow and heat transfer in the experimental set-up were simulated using computational fluid dynamics (CFD) models to understand the mechanisms responsible for performance enhancement. The CFD methodology, thus, developed was applied to understand the effect of various geometrical parameters on heat transfer enhancement. A criterion was defined for evaluation of heat transfer performance (heat transfer per unit pumping power), thus, ensuring due considerations to required pumping power. The effect of geometrical parameters and the corresponding mechanisms contributing for enhancement are discussed briefly. Based on the results, a design map comprising different serpentine channels showing heat transfer enhancement with pumping power was developed for Reynolds number of 200 which will be useful for further work on flow and heat transfer in serpentine channels. (C) 2012 American Institute of Chemical Engineers AIChE J, 59: 1814-1827, 2013
Keywords: computational fluid dynamics; heat transfer; pressure drop; serpentine